Affiliation and Control in Marital Interaction: Interpersonal Complementarity Is Present but Is Not Associated With Affect or Relationship Quality. (January 2015) - Cundiff, Jenny M.; Smith, Timothy W.; Butner, Jonathan; Critchfield, Kenneth L.; Nealey-Moore, Jill
The principle of complementarity in interpersonal theory states that an actor's behavior tends to "pull, elicit, invite, or evoke" responses from interaction partners who are similar in affiliation (i.e., warmth vs. hostility) and opposite in control (i.e., dominance vs. submissiveness). Furthermore, complementary interactions are proposed to evoke less negative affect and promote greater relationship satisfaction. These predictions were examined in two studies of married couples. Results suggest that complementarity in affiliation describes a robust general pattern of marital interaction, but complementarity in control varies across contexts. Consistent with behavioral models of marital interaction, greater levels of affiliation and lower control by partners—not complementarity in affiliation or control—were associated with less anger and anxiety and greater relationship quality. Partners' levels of affiliation and control combined in ways other than complementarity—mostly additively, but sometimes synergistically—to predict negative affect and relationship satisfaction.